Political Education for First-Time Voters: Efforts to Increase Active Participation in the 2029 Simultaneous Elections - Mahyudin, Mahyudin (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Elections are a fundamental instrument in a modern democratic system, reflecting the sovereignty of the people. Active public participation in elections is a benchmark for the success of democracy, and the quality of participation of first-time voters is crucial for the future of Indonesian democracy. This study aims to improve political understanding and active participation of first-time voters in the 2029 Simultaneous Elections. The method used was a participatory approach with the stages of problem identification, socialization, political education, interactive workshops, and evaluation and reflection. The results showed a significant increase in participants' political knowledge, with more than 80% of participants able to explain the electoral system and the role of first-time voters in democracy. Furthermore, there was a change in participants' attitudes from initially apathetic towards politics to more open and motivated to actively participate in the elections. Critical thinking and political issue analysis skills also improved, with participants able to identify hoaxes and rationally evaluate political promises. Participants' readiness to participate in the 2029 Elections also increased, with 85% stating their readiness not to abstain from voting and to participate responsibly. In conclusion, the political education provided successfully strengthened the capacity of first-time voters in facing the 2029 Simultaneous Elections and contributed to improving the quality of Indonesian democracy.